2006
DOI: 10.1128/jvi.00601-06
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Responses to Vaccinia Virus Envelope Proteins

Abstract: One approach for a safer smallpox vaccine is to utilize recombinant subunits rather than live vaccinia virus (VACV). The products of the VACV envelope genes A27L, L1R, B5R, and A33R induce protective antibodies in animal models. We propose that proteins that elicit T-cell responses, as well as neutralizing antibodies, will be important to include in a molecular vaccine. To evaluate VACV-specific memory T-cell responses, peripheral blood mononuclear cells (PBMC) from four VACV vaccinees were tested against whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Most importantly, we have detected strong reactivity to the E. coliexpressed A27L, D8L, and B5R proteins in human sera from several individuals who received Dryvax vaccination (data not shown). This observation, combined with the detection of CD4 ϩ and CD8 ϩ T-cell responses to A27L and B5R from the peripheral blood mononuclear cells of vaccinees, as reported by Tang et al (48), suggests that the triple-protein vaccination may also induce protective immunity in humans. Future studies with nonhuman primates, assessing the safety, immunogenicity, and efficacy of vaccination with E. coli-expressed A27L, D8L, and B5R proteins, will be important in determining the potential of this protein combination as a safe and effective subunit vaccine.…”
Section: Discussionmentioning
confidence: 70%
“…Most importantly, we have detected strong reactivity to the E. coliexpressed A27L, D8L, and B5R proteins in human sera from several individuals who received Dryvax vaccination (data not shown). This observation, combined with the detection of CD4 ϩ and CD8 ϩ T-cell responses to A27L and B5R from the peripheral blood mononuclear cells of vaccinees, as reported by Tang et al (48), suggests that the triple-protein vaccination may also induce protective immunity in humans. Future studies with nonhuman primates, assessing the safety, immunogenicity, and efficacy of vaccination with E. coli-expressed A27L, D8L, and B5R proteins, will be important in determining the potential of this protein combination as a safe and effective subunit vaccine.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, CD4 reactivity was documented with vaccinia ORFs A27L, L1R, B5R, and A33R, which are each targets of neutralizing Abs (58). Three epitopes were identified in A27L.…”
Section: Discussionmentioning
confidence: 99%
“…We compared CD4 Ags to those that drive human or murine HLA-transgenic CD8 ϩ responses (26,53,58,62,(73)(74)(75)(76)(77). Overall 16 ORFs (A3L, A10L, A33R, A34R, A48R, A50R, B19R, C3L, C10L, D5R, E3L, G7L, H3L, I3L, J6R, and O1L) are both CD4 and CD8 Ags.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ T cell responses were demonstrated against four envelope proteins on VV, A27L, B5R, L1R, and A33R (32). The study analyzed three class IIrestricted epitopes on A27L defined using overlapping 15-mer peptides, but did not define MHC restrictions of the epitopes, nor are the minimal epitopes outlined.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (25) have shown that, in acute infection, the CD4 ϩ T cell-dependent Ab response is more important for clearing VV using Ab-depleted and gene knockout mice. Recently, Tang et al (32) identified CD8 ϩ and CD4 ϩ responses to VV envelope proteins A27L, B5R, L1R, and A33R. They studied four VV envelope proteins expressed from mRNA in autologous dendritic cells and reported CD4 ϩ T cell responses.…”
mentioning
confidence: 99%